The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/dmrr.2560
|View full text |Cite
|
Sign up to set email alerts
|

AGEs and chronic subclinical inflammation in diabetes: disorders of immune system

Abstract: Chronic subclinical inflammation represents a risk factor of type 2 diabetes and several diabetes complications, including neuropathy and atherosclerosis including macro-vasculopathy and micro-vasculopathy. However, the inflammatory response in the diabetic wound was shown to be remarkably hypocellular, unregulated and ineffective. Advanced glycation end products (AGEs) and one of its receptors, RAGE, were involved in inducing chronic immune imbalance in diabetic patients. Such interactions attracts immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 114 publications
1
41
0
3
Order By: Relevance
“…6,7 RAGE activation is also involved in BBB damage in a variety of human brain disorders, including multiple sclerosis, diabetes mellitus, and Alzheimer disease. [8][9][10] Indeed, inflammatory responses, increased BBB permeability, and brain edema are significantly reduced after brain trauma in RAGE knockout rats. 11 Furthermore, intravenous injection of anti-HMGB1 monoclonal antibodies attenuates ischemic BBB damage.…”
mentioning
confidence: 98%
“…6,7 RAGE activation is also involved in BBB damage in a variety of human brain disorders, including multiple sclerosis, diabetes mellitus, and Alzheimer disease. [8][9][10] Indeed, inflammatory responses, increased BBB permeability, and brain edema are significantly reduced after brain trauma in RAGE knockout rats. 11 Furthermore, intravenous injection of anti-HMGB1 monoclonal antibodies attenuates ischemic BBB damage.…”
mentioning
confidence: 98%
“…, Hu et al. ). Activation of RAGE influences the development of systemic diabetic complications such as diabetic renal disease, as previously reviewed (Yan et al.…”
mentioning
confidence: 99%
“…, Hu et al . ). Recently, it has been reported that, under diabetic pulp conditions, AGEs increase mRNA expression of IL‐1β in dental pulp cells through the RAGE‐MAPK signalling pathway (Nakajima et al .…”
Section: Association Between Endodontics and Diabetes Mellitusmentioning
confidence: 97%